Die akkommodering en bestuur van diversiteit in gemeenteverband - Dreyer, T. F. J. (HTS teologiese studies, 2006)
The accommodation and management of diversity at congregational levelDiversity is becomming a prominent phenomenon of our society within a postmodern context. Many clergy and church members believe it threatens the peace and stability of churches and local congregations. Seemingly, diversity contributes to the escalation of conflict and the stress levels church leaders are experiencing. This article attempts to analize and describe the phenomenon of diversity from the angles of postmodernity, personality preferences and systems thinking. The research is based upon the hypothesis that diversity does not necessarily threaten the unity of local congregations. The manifestation of unity within diversity is only possible if leaders are sensitized to manage the challenges of pluriformity.